Dampak Persepsi Kemudahan dan Kualitas Situs Web terhadap Keinginan Konsumen untuk Membeli di Tokopedia di Universitas Sangga Buana YPKP Bandung - Ekaputra, Adriansyah; Hersusetiyati, Hersusetiyati; Ruslin, Nadya (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
This study aims to analyze the impact of perceived ease of use and website quality on consumers' purchase intention on the Tokopedia e-commerce platform at Universitas Sangga Buana YPKP Bandung. The findings indicate that both perceived ease of use and website quality have a positive and significant effect on consumers' purchase intention. Perceived ease of use has a regression coefficient of 0.640, while website quality has a regression coefficient of 0.249. The F-test shows that these two variables collectively have a significant impact on purchase intention, with an F-value of 256.029. The study concludes that to enhance consumers' purchase intention on Tokopedia, it is essential to continuously improve perceived ease of use and website quality, including user-friendly navigation, attractive design, optimal loading speed, and transaction security. Therefore, Tokopedia can be more effective in attracting and retaining consumers' purchase interest in the increasingly competitive e-commerce market.